2019
DOI: 10.1111/1462-2920.14859
|View full text |Cite
|
Sign up to set email alerts
|

Zn(II) suppresses biofilm formation in Bacillus amyloliquefaciens by inactivation of the Mn(II) uptake

Abstract: Summary Biofilms are architecturally complex communities of microbial cells held together by a self‐produced extracellular matrix. Considerable research has focused on the environmental signals that trigger or inhibit biofilm formation by affecting cellular signalling pathways; however, response to soil cues in plant‐associated Bacillus has remained largely unaddressed. Therefore, we aimed to investigate the effect of Zn(II) ions in biofilm formation of Bacillus amyloliquefaciens FZB42. We demonstrated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Combined with the reduction in epsH expression, it seems that zinc's anti-biofilm mode of action involves interfering with the construction of an extracellular matrix. A recent study demonstrated the effect of Zn 2+ ions on biofilm formation in B. amyloliquefaciens, a root-colonizing bacterium [42]. Similar to our results, the presence of zinc inhibited biofilm formation by interfering with the synthesis of the same extracellular matrix components.…”
Section: Discussionsupporting
confidence: 91%
“…Combined with the reduction in epsH expression, it seems that zinc's anti-biofilm mode of action involves interfering with the construction of an extracellular matrix. A recent study demonstrated the effect of Zn 2+ ions on biofilm formation in B. amyloliquefaciens, a root-colonizing bacterium [42]. Similar to our results, the presence of zinc inhibited biofilm formation by interfering with the synthesis of the same extracellular matrix components.…”
Section: Discussionsupporting
confidence: 91%
“…We specifically focused on four B. amyloliquefaciens traits that have previously been linked to plant growth promotion: swarming motility, biomass production, biofilm formation, and direct pathogen suppression via antibiosis ( Chen et al, 2013 ; Huang et al, 2020 ; Fira et al, 2018 ; Moreno-Velandia et al, 2019 ). While most transposon insertions reduced the strains’ performance, some of them improved at least one measured trait.…”
Section: Discussionmentioning
confidence: 99%
“…We specifically focused on four B. amyloliquefaciens traits that have previously been linked to plant growth-promotion: swarming motility, biomass production, biofilm formation and direct pathogen suppression via antibiosis (69)(70)(71)(72). While most insertions reduced the strains' performance overall, several of them were associated with improvements regarding at least one measured trait.…”
Section: Discussionmentioning
confidence: 99%
“…Increased biofilm formation was also linked to insertion in hut system ( hutU ) with one mutant, while the other mutant had insertion in YsnB gene, which encodes for a putative metallophosphoesterase. While both insertions were linked to trade-offs with swarming motility and biomass production, they are not commonly associated with biofilm formation in Bacillus (18, 70). Finally, moderate improvement in pathogen suppression was observed with two mutants that had insertions in nhaC (sodium-proton antiporter) and dfnG (difficidin polyketide synthesis) genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation